Environmental regulation, Foreign investment behavior, and carbon emissions for 30 provinces in China. (1st March 2020) - Zhang, Wei; Li, Guoxiang; Uddin, Md Kamal; Guo, Shucen
Abstract: Using the panel data of 30 provincial-level administrative regions in China (excluding Tibet, Hong Kong, Macao, and Taiwan), a threshold regression model was used to empirically analyze the impact of environmental regulation and foreign investment behavior on the amount and intensity of carbon emissions. The results showed that: First, there is a significant inverted "U"-shaped relationship between environmental regulation and carbon emissions. With improved environmental regulation, the positive effects of environmental regulation in reducing the amount and intensity of carbon emissions are more obvious. Next, foreign investment behavior under environmental regulations can reduce the amount and intensity of carbon emissions. Finally, In terms of regional heterogeneity, foreign investment behavior in the eastern and central regions can curb carbon emissions, the opposite effect is seen in the western region. With improved environmental regulations for relatively high–emission intensity regions, foreign direct investment (FDI) in low–emission intensity regions can significantly reduce carbon emissions. It is necessary to formulate differentiated environmental regulation based on regional development. Foreign investment behavior should be standardized to improve the quality of FDI and avoid making China a "pollution paradise" for FDI.